AI and Blockchain in Cybersecurity: A Sustainable Approach to Protecting Digital Assets - Sheik Mohamed; Nirmala.M; Theerka.N; Evans Dennison.J (CV.RIZANIA MEDIA PRATAMA, 2025)
The integration of Artificial Intelligence (AI) and Blockchain technology is revolutionizing cybersecurity by providing innovative, data-driven, and decentralized solutions. AI, through machine learning and deep learning, enables rapid and accurate detection of cyber threats such as malware, phishing, and zero-day attacks. Meanwhile, Blockchain ensures data integrity through its decentralized and tamper-resistant architecture, making it effective in securing sensitive information in sectors like healthcare, finance, and defense. This study explores how the convergence of AI and Blockchain can enhance cybersecurity and proposes sustainable strategies for a secure digital future. Real-world applications, such as the collaboration between the UK's National Health Service (NHS) and Google DeepMind, demonstrate the practical benefits of this integration. However, challenges remain, including data privacy concerns, infrastructure limitations, a shortage of skilled professionals, and regulatory uncertainties. The study recommends interdisciplinary research, the development of hybrid AI-Blockchain models, implementation in critical infrastructure, and strong public–private partnerships to build a resilient and scalable digital ecosystem.